Cellulase Production by Aspergillus Niger Under Solid State Fermentation Using Agro Industrial Wastes - Nur Fazlin Akmal, Muhammad Faizal (Universiti Malaysia Sarawak (UNIMAS), 2018)
Cellulose is known as one of the most dominating components in agricultural waste and abundant raw material on earth. Through cellulase enzyme that produced by filamentous fungi, helps to hydrolyze cellulose into glucose. The objctives of this research are to find out the ability of the Aspergillus niger in utilizing different types of agro industrial waste which were pineapple peel, rice husk and oil palm empty fruit bunch that act as substrates to produce cellulase, determine the best agro waste for production of cellulase by A niger and the optimum condition for the production of cellulase under solid state fermentation (SSF). Cellulases are applicable in industrial processes such as in cotton processing, detergent industries, and animal feed and ethanol production. There were three fermentation parameters that being observed which were the initial moisture content (60% - 80%), incubation temperature (25 C- 40 °C) and incubation period (2 days - 8 days). In this project, it showed that different cellulase activity was obtained for different substrates. Rice husk was shown to be the best substrates for the production of cellulase. The optimum incubation period for cellulase production using rice husk was found at day 6. Meanwhile, the optimum incubation temperature of 30 C gave the highest yield of cellulase production and the optimum initial moisture content of 60% (v/w) showed the highest amount of cellulase respectively.